Do surgeon non-technical skills correlate with teamwork-related outcomes during robot-assisted surgery?. Issue 3 (14th June 2019) - Ahmed, Youseff; Lone, Zaeem; Hussein, Ahmed A; Feng, Yingdong; Khan, Hijab; Broad, Sierra; Kannappan, Renuka; Skowronski, Alicia; Cole, Adam; Wang, Derek; Stone, Kevin; Hasasneh, Adam; et al.
Abstract : Introduction: To evaluate the impact of non-technical skills (NTS) on team performance, workload and clinical outcomes. Methods: The operating room (OR) environment of 20 robot-assisted radical prostatectomies performed by three different surgeons was recorded. Trained observers assessed NTS utilising the Non-Technical Skills for Surgeons (NOTSS) questionnaire. Associations between NOTSS scores, teamwork attributes (anticipation and inconveniences), workload (measured by National Aeronautics and Space Administration-Task Load Index (NASA-TLX)) and clinical outcomes (operative time, blood loss and surgical complexity) were determined using logistic regression and Pearson correlation. Results: 1780 requests were observed, 703 (39%) were non-verbal. Utilisation of non-verbal requests differed significantly among surgeons (26%, 36% and 44%, p<0.001). Anticipation was significantly associated with 'Situational Awareness' (OR 2.59, 95% CI 1.52 to 4.38, p<0.001), 'Decision Making' (OR 0.42, 95% CI 0.33 to 0.55, p<0.001) and 'Communication and Teamwork' (OR 0.43, 95% CI 0.25 to 0.74, p=0.002) domains. Inconveniences were significantly associated with 'Situational Awareness' (OR 0.21, 95% CI 0.08 to 0.59, p=0.003), 'Decision Making' (OR 2.73, 95% CI 1.53 to 4.86, p<0.001), and 'Leadership' (OR 0.62, 95% CI 0.41 to 0.94, p=0.03). There was a significant positive correlation between NOTSS scores and perceived physical and mental workload measures of NASA-TLX, as well as self-perceived performance. There was no significant association between NOTSS scores and any of the investigated clinical outcomes. Conclusion: NTS in the OR were associated with team efficiency, fewer surgical flow disruptions and an improved self-perceived performance.